A genetic risk score of 45 coronary artery disease risk variants associates with increased risk of myocardial infarction in 6041 Danish individuals. Issue 2 (June 2015) - Krarup, N.T.; Borglykke, A.; Allin, K.H.; Sandholt, C.H.; Justesen, J.M.; Andersson, E.A.; Grarup, N.; Jørgensen, T.; Pedersen, O.; Hansen, T.
Abstract: Background: In Europeans, 45 genetic risk variants for coronary artery disease (CAD) have been identified in genome-wide association studies. We constructed a genetic risk score (GRS) of these variants to estimate the effect on incidence and clinical predictability of myocardial infarction (MI) and CAD. Methods: Genotype was available from 6041 Danes. An unweighted GRS was constructed by making a summated score of the 45 known genetic CAD risk variants. Registries provided information (mean follow-up = 11.6 years) on CAD (n = 374) and MI (n = 124) events. Cox proportional hazard estimates with age as time scale was adjusted for sex, BMI, type 2 diabetes mellitus and smoking status. Analyses were also stratified either by sex or median age (below or above 45 years of age). We estimated GRS contribution to MI prediction by assessing net reclassification index (NRI) and integrated discrimination improvement (IDI) added to the European SCORE for 10-year MI risk prediction. Results: The GRS associated significantly with risk of incident MI (allele-dependent hazard ratio (95%CI): 1.06 (1.02–1.11), p  = 0.01) but not with CAD ( p  = 0.39). Stratification revealed association of GRS with MI in men (1.06 (1.01–1.12), p  = 0.02) and in individuals above the median of 45.11 years of age (1.06 (1.00–1.12), p  = 0.03). There was no interaction between GRS and gender ( p  = 0.90) or age ( p  = 0.83). The GRS improved neither NRI nor IDI. Conclusion: The GRS of 45 GWAS identified risk variants increase the risk of MI in a Danish cohort. The GRS did not improve NRI or IDI beyond the performance of conventional European SCORE risk factors. Highlights: This study extends the knowledge of genetic risk of coronary artery disease in Danes. A genetic risk score of 45 CAD risk-variants associate with myocardial infarction. The genetic risk score improves C-index but not reclassification by European SCORE risk factors.